Réponses

2014-01-12T22:43:19+01:00
A) 3(x+6)+2
3*x+3*6+2
3x+18+2
3x+20

B) 4+3(2y-2)
4+3*2y+3*(-2)
4+6y-6
6y-2

C) 7(2x+2)-6
7*2x+7*2-6
14x+14-6
14x+8

D) 9(x-6)+2x
9*x+9*(-6)+2x
9x-54+2x
11x-54

E) 3.5(2-x)+8.2
3.5*2+3.5*(-x)+8.2
7-3.5x+8.2
-3.5x+15.2

F) 2(3+5x)+8(7-x)+4(x-1)
2*3+2*5x+8*7+8*(-x)+4*x+4*(-1)
6+10x+56-8x+4x-4
6x+58

2014-01-12T23:24:56+01:00
A = 3 (x+6)+2
A = 3x + 18 +2
A = 3x +20

B = 4 + 3 (2y -2)
B = 4 + 6 y - 6
B = 6y -2
B = 2 (3y -1)

C = 7 ( 2x + 2 ) -6
C = 14x +14 - 6
C = 14 x +8
C = 2 (7x +4)

D = 9 (x-6) + 2x
D = 9x + 2x - 54
D = 11 x - 54

E = 3,5 (2-x ) + 8,2
E = 7 - 3,5 x +8,2
E = 15,2 - 3,5 x

F = 2 (3+ 5x) +8 (7-x) + 4(x-1)
F = 6 +10 x + 56 -8x + 4x -4
F = 6x + 58
F = 2 ( 3x + 29 )